Using The Thick-Shelled River Mussel (Unio crassus) Filtering Ability for Water Treatment Process in Aquaculture Systems: an In Vitro Study on Removal of the Bacteria from The Water - Menekşe Didem Demircan; Aygül Ekici; Gökhan Tunçelli; Merve Tınkır; İlker Keskin; Devrim Memiş (Aquatic Sciences and Engineering)
The thick-shelled river mussel (Unio crassus) is listed as 'Endangered' on the IUCN Red List of Threatened Species and it is important to culture them for the conservation of natural stocks. Integrating mussels into the freshwater aquaculture system could be an efficient method, because of their filtering ability. In this study, it was aimed to determine the bacteria filtering ability of the thick-shelled river mussel on an aquaculture system to determine if the water quality got better in terms of bacteriology. Depuration, disinfection, and antibiotic treatments were applied to reduce the bacterial load in the mussels' bodies. Disinfection was made using NaCl2 , 2-Phenoxyethanol, Formalin, Virkon® S and Chloramine T. Antibiotic treatment was performed using Oxytetracycline and Florfenicol. The best result was obtained in the group to which 5 mg L-1 Oxytetracycline was added. However, since mussels can uptake the same bacteria into own bodies with their own pseudofeces, it was found that it is appropriate to use antibiotic treatment and depuration applications together. In the experiment of keeping them in the same environment with the pathogens (Staphylococcus epidermidis, Aeromonas caviae), intense growth of bacteria was inoculated into water. Thus, it has been determined that mussels clean the water by removing bacteria from the environment within 48 hours, so river mussels can be adapted to aquaculture systems to reduce aquatic bacteria.